Mechanism of the postreceptor defect in insulin action in human obesity. Decrease in glucose transport system activity. - Ciaraldi, T P (1981)
We have studied insulin-stimulated 3-O-methyl glucose transport by isolated adipocytes prepared from 10 normal and 11 obese individuals. The results demonstrated that the insulin-glucose transport dose-response curves were shifted to the right in cells from the obese patients, and that the magnitude of this rightward shift was significantly correlated to the reduction in adipocyte insulin receptors in individual subjects (r = 0.48, P less than 0.01). In three obese patients a rightward shift in the dose-response curve could be demonstrated and there was no decrease in maximal insulin effect. This corresponded to in vivo glucose clamp results showing only a rightward shift in the insulin dose-response curve for overall glucose disposal in these three subjects (1980. J. Clin. Invest. 65: 1272-1284). In the remaining eight obese patients, the in vitro glucose transport studies showed not only a rightward shift in the dose-response curves but also a marked decrease in basal and maximally insulin-stimulated rates of transport, indicating a postreceptor defect in insulin action. Again, this was consistent with the in vivo glucose clamp studies demonstrating a marked postreceptor defect in these individuals. In conclusion, these results indicate that the mechanism of the postreceptor defect in insulin action, which exists in many obese patients, is related to a decrease in the activity of the glucose transport effector system.